Collecting and provenance - Gáldy, Andrea M.; Sorek, Ronit; Assaf, Netta; Ventura, Gal. (Newcastle-upon-Tyne : Cambridge Scholars Publisher, 2021)
This collection of essays highlights the enduring significance of provenance and its implications for historians and art historians, as well as students and researchers engaged in museum studies. It also offers an opportunity to demonstrate its relevance to other fields of expertise, such as conservation, visual culture studies, aesthetics, authentication and connoisseurship versus technology as a means of establishing attributions and detecting forgeries. Provenance is still of vital importance to jurisdiction, whether it concerns property law or ownership. It also remains topical because of it.
Chapter Twenty-Three -- Authors' Biographies -- Index
Print version record.
Includes bibliographical references and index
eBooks on EBSCOhost
Keywords: Art -- Provenance; Art -- Collectors and collecting; Antiquities -- Collectors and collecting; Museum techniques; Art -- Provenance; Art -- Collectionneurs et collections; Muséologie.; museology; provenance (history of ownership); Conservation, restoration & care of artworks; Forgery, falsification & theft of artworks; Museology & heritage studies; Antiquities -- Collectors and collecting; Art -- Collectors and collecting; Art -- Provenance; Museum techniques